Beyond net deficits: New priorities for an aquacultural geography - Belton, Ben; Bush, S.R. (Wiley, 2014)
Geographers first identified aquaculture as an important field of study during the 1990s, pointing to a ‘net deficit’ in geographical knowledge about the activity. This paper examines how far geographers have come in bridging this knowledge deficit in the last 20 years. While increasing attention has focused on the political economy of export products consumed in the global North, ‘everyday’ geographies of aquaculture production and consumption in the global South have been neglected. We argue that paying greater attention to everyday aquaculture in the global South provides opportunities for geographers to engage with wider questions around development and change that extend far beyond aquaculture. By focusing on changing patterns of aquaculture production for Southern domestic markets, geographers can provide a counterpoint to Northern dominated agro-food studies by re-emphasising the importance of consumption, urbanisation and agrarian transitions from a more place-based perspective and, in doing so, support the development of theory that reflects Southern realties.